Determination of flumazenil in serum by liquid chromatography-mass spectrometry: Application to kinetics study in acute diazepam overdose - Djordjević, Snežana B; Jović-Stošoć, Jasmina; Kilibarda, Vesna; Šegrt, Zoran; Perković-Vukčević, Nataša (Vojnosanitetski pregled, 2017)
Backgound/Aim. Flumazenil is benzodiazepine receptor antagonist. It has been studied for a various indications, including reversal of sedation after surgery or diagnostic procedures, awakening of comatose patients in benzodiazepine overdose, or for symptomatic treatment of hepatic encephalopathy. Some drugs, like theophylline, may prolong its elimination half-life. Considering the long half-life of diazepam and its metabolites, concomitant use of theophylline may reduce the need for repeated dosing of flumazenil in patients with acute diazepam poisoning. The aim of this study was to introduce a reliable and accurate method for determining the concentration of flumazenil after therapeutic application in patients with acute poisoning, and using that method to assess whether the kinetics of flumazenil change in the presence of aminophylline (combination of theophylline and ethylenediamine in a 2 : 1 ratio) applied as concomitant therapy. Methods. Blood samples from patients with acute diazepam poisoning that received flumazenil at the dose of 0.5 mg, or the same dose with 3 mg/kg of body weight of aminophylline, were collected 1, 3, 10, 30, 60, 120 and 240 min after its intravenous administration. Samples were prepared by solid-phase extraction on Oasis HLB cartridges with ethylacetate as extracting agens. Flumazenil was determined by liquid chromatography with mass spectrometry (LC-MS) in single ion monitoring mode at m/z 304. Separation of flumazenil from matrix compound was performed on Lichrospher RP-8 column using the mixture of acidic acetonitrile and 20 mM of ammonium acetate in water (55 : 45) as a mobile phase. Results. The applied analitycal method showed excellent recovery (94.65%). The obtained extracts were much cleaner than the extracts obtained by the same extractant in the process of liquid-liquid extraction. The limit of detection of the LC-MS method described in this paper was 0.5 ng/mL and the limit of quantitation was 1 ng/mL. In the patients treated with both flumazenil and aminophylline, the elimination constant for flumazenil was significantly lower and the elimination half-life was longer (p < 0.05) in comparison with the same parameters in the patients who received flumazenil alone. Conclusion. The applied LC-MS method for the determination of flumazenil in serum samples of patients with acute diazepam poisoning is rapid, sensitive, precise and specific. Concomitant use with theophylline significantly prolonged elimination of flumazenil during the treatment of acute poisonings with diazepam.
Keywords: diazepam; poisoning; flumazenil; aminophylline; chromatography; liquid; mass spectrometry